Inflammatory Cell Burden and Phenotype in Endomyocardial Biopsies With Antibody‐Mediated Rejection (AMR): A Multicenter Pilot Study From the AECVP. Issue 2 (February 2015) - Fedrigo, M.; Leone, O.; Burke, M. M.; Rice, A.; Toquet, C.; Vernerey, D.; Frigo, A.‐C.; Guillemain, R.; Pattier, S.; Smith, J.; Lota, A.; Potena, L.; et al.
<x xml:space="preserve">Abstract</x> This multicenter case‐controlled pilot study evaluated myocardial inflammatory burden (IB) and phenotype in endomyocardial biopsies (EMBs) with and without pathologic antibody‐mediated rejection (pAMR). Sixty‐five EMBs from five European heart transplant centers were centrally reviewed as positive (grade 2, n = 28), suspicious (grade 1, n = 7) or negative (n = 30) for pAMR. Absolute counts of total, intravascular (IV) and extravascular (EV) immunophenotyped mononuclear cells were correlated with pAMR grade, capillary C4d deposition, donor specific antibody (DSA) status and acute cellular rejection (ACR). In pAMR+ biopsies, equivalent number of IV CD3+ T lymphocytes (23 ± 4/0.225 mm2) and CD68+ macrophages (21 ± 4/0.225 mm2) were seen. IB and cell phenotype correlated with pAMR grade, C4d positivity and DSA positivity (p < 0.0001). High numbers of IV T lymphocytes were associated with low grade ACR (p = 0.002). In late‐occurring AMR EV plasma cells occurring in 34% of pAMR+ EMBs were associated with higher IB. The IB in AMR correlated with pAMR+, C4d positivity and DSA positivity. In pAMR+ equivalent numbers of IV T lymphocytes and macrophages were found. The presence of plasma cells was associated with a higher IB and occurrence of pAMR late after transplantation.